Government Inspectors’ Penalties and Customer Loyalty of Investment: Empirical Research based on Data of Chinese Public Companies - Lu, Ye; Li, Yubo (European Scientific Journal, ESJ, 2018)
This paper uses data of Chinese public companies from 2004-2015 to test the relationship between government inspectors’ penalties and customer loyalty of investment bank. The test results show that penalties from government inspectors would damage the reputation of investment bank and, thus, result to a decline in its market competitiveness. If the investment bank gets penalties, IPO customers would probably change the underwriters if they want to do Seasoned Equity Offering (SEO). This, therefore, result to a decline in the customer loyalty of investment bank. This negative impact of penalties on customer loyalty is more significant to the investment bank that has high reputation.